Experimental study of plasma-surface interaction and material damage relevant to ITER type i ELMs - Makhlaj, V. A.; Bandura, A.N.; Byrka, O.V.; Chebotarev, V.V.; Garkusha, I.E.; Garkusha, V.V.; Kulik, N.V.; Landman, I.; Lebedev, S.I.; Neklyudov, I.M.; Staltsov, V.V.; Tereshin, V.I. (Вопросы атомной науки и техники, 2006)
The paper presents experimental investigations of main features of plasma-surface interaction and energy transfer
to the material surface in dependence on plasma heat loads. The experiments were performed with QSPA repetitive
plasma pulses of the duration of 0.25 ms and the energy density up to 2.5 MJ/m2
. Surface morphology of the targets
exposed to QSPA plasma screams is analyzed. Relative contribution of the Lorentz force and plasma pressure gradient
to the resulting surface profile is discussed. Development of cracking on the tungsten surface and swelling of the
surface are found to be in strong dependence on initial temperature of the target.